SELANGKAH LEBIH DEKAT BERSAMA FORMATIVE ASSESSMENT - Risqi Ekanti Ayuningtyas Palupi (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2017)
Abstract Innovation and invention are the new paradigm in learning process in Indonesia. One of the innovation and invention can be seen in the quality of teaching learning process. Meanwhile, the quality of teaching learning process can be measured by having a measurement called as evaluation or assessment. Based on the process of assessment, it can be divided into two terms; formative and summative assessment. Lecturers usually use summative assessment to make a grading but they forget that the process of learning processes also need an evaluation, here called formative assessment. This assessment is used to measure the students’ achievement in learning process. This research is aimed to describe the efforts in implementing the formative assessment in reaching the learning goals. This research was done in English Department in private universities; Muhammadiyah University of Ponorogo and STKIP PGRI Ponorogo. This is a qualitative research. The result of this research is the lecturers of both universities had done this formative assessment although not all of them use the result of the formative assessment. They used this to measure the students’ understanding of the lesson. They usually use one to one assessment, small group assessment, and then a field trial in implementing their formative assessment.Keywords: Formative assessment